Prey-Carrying Behavior of Lycalopex Foxes in Chilean Patagonia - Moreira-Arce, D (Elsevier Inc., 2024)
This study examines prey-carrying behavior in culpeo (Lycalopex culpaeus) and chilla (L. griseus) foxes within Chilean Patagonia s sheep farming lands. We used camera traps to register prey transportation. This behavior was more frequent during the reproductive season compared to the non-reproductive season, suggesting an association with pup-rearing activities. The presence of livestock guardian dogs and other predation control measures may also influence prey-carrying behavior, particularly in L. culpaeus, as foxes might adjust their activities in response to perceived risks. This research provides initial evidence of prey transport in these fox species and highlights the need for further study to understand its ecological implications and interactions with livestock management practices. © 2024